Posted by **Alice v** on Friday, June 4, 2010 at 12:12am.

-12x^6+24x^5-18x^2/-6x^2

3x^4+x^3-3x

check see if I did it right.

- algebra -
**Reiny**, Friday, June 4, 2010 at 7:20am
If you meant to type

(-12x^6+24x^5-18x^2)/(-6x^2) , then

= 2x^4 - 4x^3 + 3

If the question is the way you typed it, that is, only the last term is divided by -6x^2 you would get

-12x^6 + 24x^5 + 3

there is no logical way of interpretation of your question to get your answer.

## Answer this Question

## Related Questions

- algebra - -12X^6+24x^5-18x^2/-6x^2=2x^4+24x^3-3x could some one check this for ...
- algebra - 24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3...
- Algebra - checking problem Use FOIL to multiply: (6x – 1)(3x – 4) 6x*3x + 6x*(-4...
- math - -12x^6+24x^5-18x^2/-6x^2= -4x^8+4x^7-3x tell me if this right
- algebra - Reduce answers to lowest terms. 1.) 2x/2x^2+5x-3 + 5/x^2-9 = 2.) x-3/...
- BobPursley..here it is: - Problem 1: (x-2)/(3x+4) - 6x/(x+1) What I did: Common ...
- alg2 check? - solve 3(8x-2)=46-2(12x+1) 24x-6=46-24x+2 24x-6=48-24x 48x-6=48 48x...
- Math - (2x-1)(3x-7)(4x+3) =6x^2-14x-33x+7 =(6x^2-19x+7)(4x+3) =24x^3+18x^2-126x+...
- Math - Hello, Having trouble with this one... Solve the inequality: (2x-3)(4x)+x...
- Algebra (Re.: Reiny) - The fact that there was that nice symmetry to the ...